Assessment of tear drainage by fluorescein dye disappearance test after experimental canalicular obstruction - (:unkn) unknown (My University, 1993)
Abstract Controversy exists about the role of upper and lower canaliculi in tear drainage. Fluorescein dye disappearance test was used to evaluate tear drainage after experimental obstruction of upper, lower, neither or both canaliculi in 18 subjects by hydroxypropil cellulose rods. When both canaliculi were occluded marked impairment was noted in all subjects (p < 0.05). Monocanalicular obstruction (either upper or lower) generally resulted in minimal impairment in most of the cases. Only 11% of upper canilicular obstruction and 20% of lower canalicular obstruction resulted in marked impairment. There was no significant difference between upper and lower canalicular obstruction (p < 0.05). In this study it is concluded that both upper and lower canaliculus have equal importance in tear drainage. 1993 Institution Acta Ophthalmologica Scandinavica
Keywords: canalicular obstruction; fluorescein dye test; hydroxypropil cellulose; lacrimal canaliculus; tear drainage